A Thing-bound Approach to the Practice and Teaching of Technical Translation - Folkart, Barbara (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1984)
AbstractThe raison d'être of the technical text is in the access it affords to its referents. It follows that technical translation involves reverbalizing these referents rather than mapping semiotic structures from source-to target-language, as is the case with the other, more "hybrid" forms of discourse, in which functions of language other than the purely referential play a role. The source-language formulation is thus relatively unimportant. In the extreme case, which is not necessarily that of a poorly written source text, it can even be bypassed altogether, the translator drawing his information from the non-linguistic segments of the source text (equations, diagrams and the like) and verbalizing it directly in the target language.For Ivan Hirst, from whom I learned most of what I know about technical translation. The technical translator's stock in trade is an in-depth understanding of the referent. The following article proposes a number of teaching strategies designed to sensitize non-specialist students to the importance of the referent, to help them acquire the minimal background they will need to deal with texts in a given field and to enable them to reduce technical texts to their underlying referents.